Modern Era Da’wah Problems Perspective Surat Taha: 44 - Aris Yusuf, Mochamad; Viruliana, Fajrina Margareth; Fikri, Alwanul (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2023)
With the increasing presence of digital media, the challenges of proselytizing faced by Muslims are also increasingly complex which can haunt Muslims who often access the media. Therefore, the author reveals a phenomenon intertwined in proselytizing activities with the perspective of Taha verse 44. This research is a descriptive qualitative research based on library research. The results of this study revealed that when carrying out proselytizing activities, a da'i should have a good personality, because the success and strength of a proselytizing depends on the person of the proselytizer himself. In the letter of Taha: 44, there is a story of the journey of the prophet Moses and the Prophet Aaron who were commanded by Allah Almighty to provide good education to Pharaoh. The verse explains how important it is as preachers to choose the right method of preaching, namely through rhetoric or meek words. Therefore, meekness is a shaky attitude that is always in demand among many people. So that with that trait will give birth to tranquility and peace for both da'i and mad'u perpetrators. Dengan kehadiran media digital yang semakin tinggi, tantangan dakwah yang dihadapi umat Islam juga semakin kompleks yang dapat menghantui umat Islam yang sering mengakses media. Oleh karena itu, penulis mengungkapkan fenomena yang terjalin dalam aktifitas dakwah dengan perspektif surat Thaha ayat 44. Penelitian ini merupakan penelitian kualitatif deskriptif dengan berbasis penelitian perpustakaan. Hasil penelitian ini mengungkapkan bahwa saat melaksanakan aktivitas dakwah, seorang da’i hendaknya memiliki kepribadian yang baik, sebab kesuksesan dan kekuatannya suatu dakwah sangat bergantung kepada pribadi dari pembawa dakwah itu sendiri. dalam surat Taha: 44, terdapat kisah perjalanan nabi Musa dan Nabi Harun yang diperintahkan oleh Allah SWT untuk memberikan edukasi yang baik kepada Fir’aun. Dalam ayat tersebut dijelaskan betapa pentingnya sebagai para pendakwah memilih metode yang tepat dalam menyampaikan dakwah, yakni melalui retorika atau perkataan yang lemah lembut. Oleh karena itu lemah lembut adalah sikap syahdu yang selalu diminati dikalangan banyak orang. Sehingga dengan sifat itu akan melahirkan ketenangan dan kedamaian baik bagi pelaku da’i maupun mad’u.